2023
DOI: 10.1002/ejhf.2891
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of sodium–glucose cotransporter 2 inhibitors in patients with heart failure with preserved ejection fraction: From outcome improvement to potentially favourable influences on atrial fibrillation burden, atrial fibrillation progression and atrial cardiomyopathy

Abstract: This article refers to 'Empagliflozin in heart failure with preserved ejection fraction with and without atrial fibrillation' by G. Filippatos et al., published in this issue on pages 970-977.Atrial fibrillation (AF) and heart failure (HF) frequently coexist, but the link is particularly tight in HF with preserved ejection fraction (HFpEF). Taking into account the whole spectrum of HF patients, the prevalence of AF appears to be higher when HF is diagnosed in association with higher values of left ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…This trial demonstrated that dapagliflozin could reduce the incidence of reported episodes of AF/AFL adverse events, especially in high-risk patients with T2DM. This finding underscores the potential role of dapagliflozin in reducing AF in populations at heightened cardiovascular risk (Boriani et al, 2023).…”
Section: Clinical Evidencesupporting
confidence: 52%
See 2 more Smart Citations
“…This trial demonstrated that dapagliflozin could reduce the incidence of reported episodes of AF/AFL adverse events, especially in high-risk patients with T2DM. This finding underscores the potential role of dapagliflozin in reducing AF in populations at heightened cardiovascular risk (Boriani et al, 2023).…”
Section: Clinical Evidencesupporting
confidence: 52%
“…• Observational evidence: Multiple observational studies have reported a consistent association between SGLT2 inhibitor use and a reduced risk of AF in individuals with type 2 diabetes mellitus (T2DM) and heart failure. This suggests a potential protective effect of these medications against AF (Lee et al, 2021;Boriani et al, 2023;Zelniker et al, 2020).…”
Section: Af Risk Reductionmentioning
confidence: 91%
See 1 more Smart Citation
“…• Observational Evidence: Multiple observational studies have reported a consistent association between SGLT2 inhibitor use and a reduced risk of AF in individuals with type 2 diabetes mellitus (T2DM) and heart failure. This suggests a potential protective effect of these medications against AF (60,61,62).…”
Section: Af Risk Reductionmentioning
confidence: 91%
“…In 2023, Giuseppe Boriani initiated a comprehensive study, demonstrating that empagliflozin yielded a significant reduction in the risk of severe heart failure events and a deceleration in the decline of estimated glomerular filtration rate (eGFR), irrespective of the presence of atrial fibrillation, in patients with heart failure and an ejection fraction greater than 40%. (61).…”
Section: Renal Hemodynamicsmentioning
confidence: 99%